2013
DOI: 10.1111/1574-6941.12126
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the deep biosphere: retrieving authentic microbial communities from packer-isolated deep crystalline bedrock fracture zones

Abstract: Deep fracture zones in Finnish crystalline bedrock have been isolated for long, the oldest fluids being tens of millions of years old. To accurately measure the native microbial diversity in fracture-zone fluids, water samples were obtained by isolating the borehole fraction spanning a deep subsurface aquifer fracture zone with inflatable packers (500 and 967 m) or by pumping fluids directly from the fracture zone. Sampling frequency was examined to establish the time required for the space between packers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 53 publications
(92 reference statements)
4
77
0
Order By: Relevance
“…Earlier research of the Fennoscandian deep subsurface has demonstrated its potential for monitoring changes in microbial community composition at different depths over time and for screening samples prior to the construction of clone libraries or metagenomic work [2] [5] [13]. However, despite use of two universal bacteria primer pairs, DGGE appeared to be biased towards Proteobacteria, especially the γ-and β-groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier research of the Fennoscandian deep subsurface has demonstrated its potential for monitoring changes in microbial community composition at different depths over time and for screening samples prior to the construction of clone libraries or metagenomic work [2] [5] [13]. However, despite use of two universal bacteria primer pairs, DGGE appeared to be biased towards Proteobacteria, especially the γ-and β-groups.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest part of the archaeal 16S rRNA gene sequences (52%, 81% and 58% in OL-KR40/385m, OL-KR49/532m and OL-KR40/ 609m, respectively) belonged to uncultured Thermoplasmatales (Table 3(b)). 13.7% of the archaeal community in OL-KR40/385m clustered with cultured Thermoplasma species. Pendant 33/DHVE3, 4, 6 archaea was a major group in OL-KR40/609m (47.3%), but was only minor or absent in the other samples.…”
Section: Amplicon Library Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…Once a well has been developed, U -tube borehole fluid samplers can be used to remove the drilling fluid or monitor its dilution over time with ground water flow and then collect true formation fluids and gasses at near in situ conditions (Freifeld, 2009; Stotler et al, 2011). Further, geochemical conditions and microbial community structures for specific fractures can be determined through the use of packers that isolate those fractures within a borehole for sampling (Haveman et al, 1999; Shimizu et al, 2006; Purkamo et al, 2013). Finally, significant understanding of the mineralogy and geochemistry of a subsurface environment can be derived from the effective utilization of well log data (Onstott et al, 1998).…”
Section: Sample Collection and Contamination Assessmentmentioning
confidence: 99%